WAVES: Soft-Material Based Adaptable Walking-Type Stair-Climbing Robot for Various Step Sizes - Sungjun Park; Jeongpil Shin; Younghwan Kim; Taewon Seo (IEEE Access, 2024)
Existing state-of-the-art stair climbing robots require precise control through many sensors and actuators to climb various stairs. In this study, we propose WAVES, a stair-climbing robot that can climb a variety of stairs with minimal electronic components and control. WAVES’ stair climbing ability is due to its soft part on the bottom, which adapts passively to the shape of the stairs. The soft parts were fabricated into a compliant mesh shape and could be freely deformed according to the shape of the stairs. We used the ratio of horizontal and vertical reaction forces that occur when the soft part is deformed as an index to determine stability, and the simulation results showed that the arc shape has the smallest horizontal reaction force ratio of 0.224 (honeycomb: 0.303, spoke: 0.276). Also, to determine the appropriate strength of the soft parts, we calculated the maximum compressive force that each section of the soft part should withstand. Based on the calculation results, we made the gap between arc patterns closer where the strong compressive force is applied. In conclusion, before applying soft parts to the robot, the diagonal length of the stairs it could climb was 328.7 mm–350 mm, but after applying soft materials, it can climb all stairs under 400 mm.